Toxicity profiles of ROS1 tyrosine kinase inhibitors in advanced non-small cell lung cancer: a systematic review and proportional meta-analysis - Jiang, Bo-Xuan; Zeng, Jia-Wei; Yan, Jia-Jia; Zhao, Li-Yan (Frontiers in Pharmacology, 2025)
ROS1 tyrosine kinase inhibitors (TKIs) have shown significant efficacy in advanced ROS1-rearranged non-small cell lung cancer (NSCLC). However, no systematic investigation has been conducted on the toxicity profiles of these TKIs, which are critical for clinical decision-making and patient management. We conducted a systematic search across PubMed, Embase, the Cochrane Library, and ClinicalTrials.gov to identify studies that reported on the safety profiles of ROS1-TKIs in patients with advanced NSCLC. Eligible studies were those published between 1 January 2013 and 28 February 2025 in English language. A proportional meta-analysis was performed. Primary outcomes included the incidence rates of systemic all-grade adverse events (AEs; grades 1–5) and serious adverse events (SAEs; grades 3–5) for each ROS1-TKI, while secondary outcomes focused on incidence rates of specific AEs and SAEs. This systematic review and proportional meta-analysis included 26 studies involving 5,273 patients. ROS1-TKIs demonstrated high incidences of systemic all-grade AEs, ranging from 90% to 99%. Systemic SAEs exhibited greater variability across agents, ranging from 29% to 47%: crizotinib, 43% (95% CI, 36%–49%); ceritinib, 41% (95% CI, 37%–45%); lorlatinib, 39% (95% CI, 25%–55%); entrectinib, 32% (95% CI, 28%–36%); repotrectinib, 29% (95% CI, 24%–33%); iruplinalkib, 44% (95% CI, 38%–50%); and unecritinib, 47% (95% CI, 38%–56%). This indicated that repotrectinib might be more tolerable, while unecitinib might have a lower safety profile. Additionally, specific AE profiles varied across ROS1-TKIs: repotrectinib exhibited higher rates of dizziness, entrectinib demonstrated frequent fatigue, and lorlatinib showed an increased incidence of edema. Taletrectinib and unecritinib were notably associated with hepatotoxicity. This study presents the first comprehensive evaluation of ROS1-TKIs’ toxicity profiles in NSCLC patients. These findings will guide drug selection and safety monitoring, emphasizing the necessity of considering patients’ health status, potential risk factors, and the characteristics of ROS1-TKI-related adverse reactions.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024551353, identifier CRD42024551353.